Memory-guided attention: bilateral hippocampal volume positively predicts implicit contextual learning - Rosero Pahi, Mario Alberto; Winkelmann, Tobias; Pohlack, Sebastian; Cavalli, Juliana; Nees, Frauke; Flor, Herta (Brain structure & function, 2019)
Several studies have begun to demonstrate that contextual memories constitute an important mechanism to guide our attention. Although there is general consensus that the hippocampus is involved in the encoding of contextual memories, it is controversial whether this structure can support implicit forms of contextual memory. Here, we combine automated segmentation of structural MRI with neurobehavioral assessment of implicit contextual memory-guided attention to test the hypothesis that hippocampal volume would predict the magnitude of implicit contextual learning. Forty healthy subjects underwent 3T magnetic resonance imaging brain scanning with subsequent automatic measurement of the total brain and hippocampal (right and left) volumes. Implicit learning of contextual information was measured using the contextual cueing task. We found that both left and right hippocampal volumes positively predicted the magnitude of implicit contextual learning. Larger hippocampal volume was associated with superior implicit contextual memory performance. This study provides compelling evidence that implicit contextual memory-guided attention is hippocampus-dependent.